Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1098/rspb.1999.0859
|View full text |Cite
|
Sign up to set email alerts
|

Egg puncture allows shiny cowbirds to assess host egg development and suitability for parasitism

Abstract: Parasitic cowbirds and cuckoos generally reduce the clutch size of the hosts they parasitize by removing or destroying some of their eggs. Shiny cowbirds (Molothrus bonariensis) puncture their hosts' eggs both when parasitizing the nests and also when they do not parasitize them. We propose that, by puncturing the host's eggs, shiny cowbirds gain an informational bene¢t. They assess the degree of development of the host's embryos and so avoid laying in nests that would not provide enough incubation time for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 29 publications
0
14
0
1
Order By: Relevance
“…If a host can prevent parasitism through nest defence, it saves its entire clutch. If it delays defence until the egg stage, it will have lost some of its clutch because the cuckoo usually removes one or more host eggs before it lays (Davies & Brooke, 1988) or it may puncture host eggs (Soler, Soler & Martinez, 1997; see also Massoni & Reboreda, 1999; Spottiswoode & Colebrook‐Robjent, 2007). If the host delays further, until the chick stage, it will have probably lost its entire clutch (ejector cuckoos) or at least some of its clutch or brood (non‐ejector cuckoos).…”
Section: Trickery: Adaptation and Lack Of Adaptationmentioning
confidence: 99%
See 1 more Smart Citation
“…If a host can prevent parasitism through nest defence, it saves its entire clutch. If it delays defence until the egg stage, it will have lost some of its clutch because the cuckoo usually removes one or more host eggs before it lays (Davies & Brooke, 1988) or it may puncture host eggs (Soler, Soler & Martinez, 1997; see also Massoni & Reboreda, 1999; Spottiswoode & Colebrook‐Robjent, 2007). If the host delays further, until the chick stage, it will have probably lost its entire clutch (ejector cuckoos) or at least some of its clutch or brood (non‐ejector cuckoos).…”
Section: Trickery: Adaptation and Lack Of Adaptationmentioning
confidence: 99%
“…She also depredates host clutches too late to parasitize (where incubation has already begun), which then makes the host's replacement clutch available for parasitism (Gärtner, 1981; Gehringer, 1979). It would be interesting to know whether female cuckoos identify these advanced clutches by pecking eggs to test their stage of development (as cowbirds do, Massoni & Reboreda, 1999), or whether they use cues from host behaviour (e.g. incubation).…”
Section: Tuning Into Host Life Historiesmentioning
confidence: 99%
“…The hatching and fledging success of nests in which we removed cowbirds eggs were similar to those of parasitized nests. This result is not totally surprising, given that one of the main costs suffered by hosts of the cowbird is egg puncture, which occurs before or during the parasitism event (Mermoz and Reboreda 1994, Massoni and Reboreda 1999. On the other hand, nest desertion was also associated with cowbird parasitism, but this behavior is likely a response to an abnormal clutch size due to multiple parasitism events (i.e., the nest received >1 cowbird egg), to egg losses due to egg punctures (Rothstein 1975;Fraga 1978Fraga , 1983, or to disturbance resulting from increased activity of cowbirds at the nest, rather than constituting a specific antiparasite response.…”
Section: Figmentioning
confidence: 85%
“…Similarly, Peer and Sealy (1999) suggested that Bronzed Cowbirds puncture host eggs to force renesting. Yet another hypothesis to explain egg punctures in nests that are not subsequently parasitized is that cowbirds do so to assess the degree of embryonic development of the egg, and use this information to decide whether to parasitize a nest (test‐incubation hypothesis; Livesey 1936, Massoni and Reboreda 1999).…”
mentioning
confidence: 99%